The Role of Some Enzymes and Vitamin C in Diagnosis of Ovarian Cancer in Iraqi Patients - Dawood, Noor L.; Hassan, Firas A. (Iraqi Journal of Science, 2025)
Ovarian cancer stands out as the most lethal gynecological cancer, characterized by its aggressive nature, which is largely attributed to the fact that it is often diagnosed at a late stage. Patients with ovarian cancer, particularly those with early-stage tumors, currently face challenges in obtaining a clear and efficient pre-surgical diagnosis. This paper aimed to determine the role of acetyl-CoA carboxylase, fatty acid synthase, matrix metalloproteinase-14, and Vitamin C in patients with ovarian cancer. One hundred patients diagnosed with ovarian cancer at Al-Amal Hospital for Radiation and Nuclear Medicine and Oncology Teaching Hospital at Baghdad Medical City aged from 35 to 65 years were included in this study, divided into 50 patients untreated as a group I, and 50 patients treated as group II and 40 healthy women as a control group. The findings revealed a notable increase in the concentrations of acetyl-CoA carboxylase, fatty acid synthase, and matrix metalloproteinase-14 (P-value <0.0001) among patients with ovarian cancer compared to the control group. In contrast, vitamin C concentration was significantly lower than in the control group, (P-value <0.0001). A receiver operating character curve analysis showed a high sensitivity according to the area under the curve. The present results conclude that acetyl-CoA carboxylase, fatty acid synthase, and matrix metalloproteinase-14 can be used as biomarkers for early-stage detection diagnostic markers for ovarian cancer.